2010
DOI: 10.1007/s00226-010-0306-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of chlorine-labelled chitosan in Scots pine by energy-dispersive X-ray spectroscopy

Abstract: The aim of this study was to use energy-dispersive X-ray spectroscopy (EDX) to localize chitosan in the cell wall of chitosan-impregnated Scots pine. It was of interest to investigate the concentration of chitosan in wood to gain further knowledge and understanding of the distribution of chitosan in the wooden matrix. After deacetylation, chitosan was re-acetylated with chloroacetic anhydride to achieve a covalent bonding of chloride to the chitosan polymer. Chloride-labelled chitosan was measured by EDX using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…For instance, calculated from vacuum treated sample with 1 % chitosan solution, C1 had 100 % relative content while the relative content of C3 was approximately 78 %. Larnøy et al (2010) reported a similar result showing that the higher Mw of chitosan had better fixation in wood. This can be explained by the DP n of chitosan which decides Mw of chitosan.…”
Section: The Concentrations Of Chitosan and Silicon In The Wood Samplessupporting
confidence: 69%
“…For instance, calculated from vacuum treated sample with 1 % chitosan solution, C1 had 100 % relative content while the relative content of C3 was approximately 78 %. Larnøy et al (2010) reported a similar result showing that the higher Mw of chitosan had better fixation in wood. This can be explained by the DP n of chitosan which decides Mw of chitosan.…”
Section: The Concentrations Of Chitosan and Silicon In The Wood Samplessupporting
confidence: 69%
“…The reduction of mechanical properties could be attributed to an excessive amount of glutaraldehyde in these LS/CS‐Glu adhesives. In the case of wood fiber composites reinforced with chitosan, some researchers suggested that the adhesion between the wood fibers and chitosan was due to the hydrogen bonds, CN linkages, and electrostatic/ionic interactions between the amino groups in chitosan and the hydroxyl groups in wood fibers . The reaction between chitosan and glutaraldehyde was mainly due to the reaction of amino groups of chitosan with aldehydic groups of glutaraldehyde .…”
Section: Resultsmentioning
confidence: 99%
“…Effectively, high‐molecular CS polymer is known to be quite flexible in an aqueous solution. Moreover, Larnøy et al14 showed that media with high‐molecular weight CSs can elasticate into cell wall, enter into intercellular capillary spaces, and expend, thus being trapped. A microimaging technique was used to visualize the fine wood structure as well as the penetration level of a solution of rhodamine‐labeled CS at 4% (w/v).…”
Section: Resultsmentioning
confidence: 99%
“…It has received wide attention for several commercial applications as it is one of the highest abundant biopolymer on earth after cellulose 5,6. The main developments of bioadhesives were carried out in the biomedical field7–9 and more recently in wood industry 10–14. Parameters influencing the attractive characteristics of CS in the field of adhesives are its molecular weight ( M w ) as well as its degree of DD.…”
Section: Introductionmentioning
confidence: 99%